2022
DOI: 10.5590/jsbhs.2022.16.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Information About COVID-19 Among Older Adults in Ghana, 2019-2021

Abstract: The COVID-19 pandemic sparked a worldwide search for information. Information about COVID-19 is crucial and it could be the first step toward designing practical disease-control strategies. Misinformation amid the widespread information about COVID-19 has undoubtedly caused psychological distress, especially among older adults. We present an empirical and descriptive study of the sources of information among older adults and how they perceived the COVID-19 pandemic. A total of 58 participants were recruited an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study further found that people were seeking information from family members and friends. Another study by Adu-Gyamfi and Asante, (2022), indicated that television programs, family, friends, and churches were the most used sources for providing educational information on COVID-19. Parents are an important group that could influence one to make a decision in following COVID-19 preventive measures, such as hand washing behaviours and vaccine acceptance (Costantini, 2021;de Maio Nascimento, 2020).…”
Section: Covid-19 Information Sources Used By the General Publicmentioning
confidence: 99%
“…The study further found that people were seeking information from family members and friends. Another study by Adu-Gyamfi and Asante, (2022), indicated that television programs, family, friends, and churches were the most used sources for providing educational information on COVID-19. Parents are an important group that could influence one to make a decision in following COVID-19 preventive measures, such as hand washing behaviours and vaccine acceptance (Costantini, 2021;de Maio Nascimento, 2020).…”
Section: Covid-19 Information Sources Used By the General Publicmentioning
confidence: 99%
“…Ghana’s government widely uses social media systems to communicate COVID-19-related information to the general public and social media systems remained a vital source of information for the Ghanaian public about COVID-19 pandemic management information( Adu-Gyamfi and Asante, 2022 ; Britwum et al, 2023 ). Eyifah (2021) noted that 59.5% of Ghanaians use social media systems, particularly Facebook and WhatsApp as the main source to obtain information related to the COVID-19 pandemic management.…”
Section: Introductionmentioning
confidence: 99%